Pendampingan Baca Tulis Pegon di Pondok Pesantren Idhotun Nasyi’in Sugihwaras Kalitengah Lamongan - Khoirun Nisa; Ahmad Izzuddin; Maslakhul Falakh; Mohammad Farid Syarifuddin; Nia Elsa Qotrunnada Khofsoh; Shofi Alam Sari (Santri: Journal of Student Engagement, 2022)
The yellow book or salaf book is a term of the book that is often studied in various Boarding Schools, including in the Idhotun Nasyi'in boarding school. In the study santri must be able to write the teacher's translation using pegon. Therefore, the students must first know and learn how to read pegon writing. But pegon learning in this boarding school is still fairly less effective, even rarely done. That's why this assistance is done to maximize the assets and potential that santri has, especially in pegon learning so that they can write it properly and correctly. That's why this assistance is done to maximize the assets and potential that santri has, especially in pegon learning so that they can write it properly and correctly. This assistance is expressed using the ABCD (Asset Based Community Development) method with several stages including: discovery, dream, define, design, and desnity. The desnity stage is divided into four activities: the first activity is the introduction of pegon letters in the students, the second activity is how to string words using pegon letters, the third activity is to recognize and memorize the symbol of tarkib in the meaning of the yellow book, and the last is evaluation. As for the results obtained from this assistance slowly santri who can not write pegon finally able to write it properly and correctly. So in the last evaluation, four of the six students have met the standard of ability and the remaining two have not. These two students will be followed up and supported to continue learning and practicing pegon writing until it becomes good and true.